GOOD GOVERNANCE INITIATIVE IN THE LESS DEVELOPMENT COUNTRIES - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
For the European Union and UNDP (2006), the quality of governance is ultimately attributed to its democratic content. Thereby the promotion of ‘democratic governance’ is a core element in their development assistance strategy. UNDP argues that human development and governance are inseparable. From the human development perspective UNDP has stated that ‘good governance’ is ‘democratic governance. According to Brandi (2008), Democratic Governance is the glue that holds all the other development priorities set out across the MDG’s together. In post-conflict societies it is much advocated by the international community that democratic systems provides the best mechanisms for reconciliation and are the best guarantors of lasting peace (Brandi &Clara, 2008). According to Boex, Kimble and Pigey (2010), a government is essential to providing security, justice, economic, and social functions and to channeling the will, energies, and resources of both the indigenous population and the international community. According to Shah (2006), governments support peace building through encouraging institutional participation in peace building and democratic process of their countries.